Theoretical and experimental study on the thermomechanical characteristics of double-row angular contact automotive wheel bearings - Dong Yanfang; He Kai; Qiu Ming; Yan Zibo; Yu Wei (Scientific Reports)
Abstract The thermodynamic characteristics of double-row angular contact wheel bearings are important for the bearing operational condition monitoring and structural design. The load distribution and power consumption distribution of the bearing are obtained by establishing a thermal-force coupling model of the double-row angular contact wheel bearing. Combining with the thermal network and finite element analysis method, the steady-state temperature field of the bearing under test conditions is achieved. Also a box-type encapsulated fiber-optic grating temperature sensor is designed for investigating the effects of working condition parameters on the axial and circumferential temperature distributions of the bearing. And a comparative analysis with the predicted results is carried out. The results show that there are obvious temperature differences in the axial and circumferential direction of double-row angular contact wheel bearing under combined load. The speed, axial force and radial force all affect the bearing temperature rise and temperature distribution.